An application of aromatic compounds as alternative tracers of tsunami backwash deposits. Issue 4 (April 2021) - Pongpiachan, Siwatt; Surapipith, Vanisa; Hashmi, Muhammad Zaffar; Aukkaravittayapun, Suparerk; Poshyachinda, Saran
Abstract: This manuscript provides some comprehensive technical insights regarding the application of polycyclic aromatic hydrocarbons (PAHs) characterized by using Gas-Chromatography Mass Spectrometry. Although numerous chemical species such as water soluble ionic species (e.g. Na +, K +, Cl −, Ca 2+, Mg 2+ ) and acid leachable heavy metal fractions (e.g. Fe, Cd, Al, Mo, Sb, As, Cu, Zn, Pb, and Mn) can be used to characterize tsunami deposits, the knowledge of PAH congeners as alternative chemical species for identifying tsunami backwash deposits is strictly limited. This manuscript is exclusive because it aims to find some alternative chemical proxies in order to distinguish tsunami backwash deposits from typical marine sediments. A wide range of diagnostic binary ratios of PAH congeners have been selected in order to characterize Typical Marine Sediments (TMS), Tsunami backwash deposits (TBD), Onshore Tsunami Deposits (OTD) and Coastal Zone Soils (CZS). The state of the art and future perspectives coupled with both advantages and disadvantages of above mentioned chemical tracers will be critically reviewed and further discussed. Abstract : Marine sediments, Polycyclic aromatic hydrocarbons (PAHs), Andaman Sea, Diagnostic binary ratios, Chemical tracers.